DETERMINING FACTORS THAT EFFECTING MSMEs BANK CREDIT ACCESS - Febriastuti, Seli; Herwiyanti, Eliada; Ulfah, Permata (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2023)
The study aims to determine the effect of factors that effecting bank credit access for MSMEs in Purbalingga Regency with financial literacy as a moderating variable. The population in this study are SMEs in the fashion sector in the Segamas Market, Purbalingga Regency. The samples in this study were 96 businesses used the total sampling method. Data analysis used multiple linear regression and moderated regression analysis.The results of this study indicate that: (1) credit knowledge has a positive effect on access to bank credit; (2) banking service quality has no positive effect on bank credit access; (3) business continuity has no positive effect on access to bank credit; (4) financial literacy does not moderate the effect of credit knowledge on bank credit access; (5) financial literacy does not moderate the effect of banking service quality on bank credit access; (6) financial literacy does not moderate the effect of business continuity on bank credit access. The implication of this research for MSMEs it can provide an overview of the importance of credit knowledge and financial literacy in accessing bank credit. Meanwhile, the Purbalingga Regency Cooperative and UKM Service can provide an overview of financial training for MSMEs.